Edge Computing in Context Awareness: A Comprehensive Study - V. Mahalakshmi; B. Karthikeyan (Engineering Proceedings)
Mobile edge computing (MEC), which is now gaining a lot of momentum, allows users to use its services with low latency, location awareness, and mobility assistance to offset the drawbacks of cloud computing. The quality of the experience, reduced latency, and boosted performance are the ultimate context-aware goals. There have been many context-aware efforts in the past. In this study, we reviewed many elements of the proposed context-aware approach for edge cloud computing, including their benefits and drawbacks. Additionally, we looked at such context-aware techniques to determine which were practical given the situation. We anticipate that the survey will be carefully considered in the creation of new context-aware methods. Future directions and problems have also been looked at.